Antibacterial Susceptibility of Clinical Isolates of Klebsiella pneumoniae in Nigeria to Carbapenems - Oladipo, Elijah Kolawole; Awoyelu, Elukunbi Hilda; Adeosun, Idowu Jesulayomi; Ayandele, Abiodun A (Iraqi Journal of Science, 2021)
The emergent bacterial resistance to antibiotics, most especially Carbapenems, has become a common phenomenon. The aim of the recent study was the observation and evaluation of the antibacterial susceptibility of Klebsiella pneumoniae in clinical specimens to different Carbapenems. One hundred isolates of K. pneumoniae isolated from different clinical sites, such as leg, caesarean section (CS), head, buttock, breast, thigh, and arm were tested. Using disc diffusion method, the isolates were tested for susceptibility to different antibiotics including Tobramycin, Ciprofloxacin, Aztreonam, Colistin sulphate, Ceftriaxone, Cefepime, Cefoxitin, Ceftazidime, Ertapenem, Meropenem, and Imipenem. The results were interpreted according to the Clinical and Laboratory Standard Institute disk diffusion standard. All K. pneumoniae isolates were highly susceptible to all classes of Carbapenems: Imipenem (99%), Meropenem (96%) and Ertapenem (91%). However, they were highly resistant to Ciprofloxacin (97%), Ceftriaxone (91%) and Tobramycin (73%). Despite the recent emergence of multi-drug resistant bacteria to Carbapenems, this study showed that Carbapenems could still be used in treating different infections caused by multi-drug resistant K. pneumoniae.